Characterization of Staphylococcus aureus Isolates That Colonize Medical Students in a Hospital of the City of Cali, Colombia - Luis Fernando Collazos Marín; Gina Estupiñan Arciniegas; Monica Chavez Vivas (International Journal of Microbiology)
Introduction. Nasal carriage of methicillin-resistant Staphylococcus aureus (MRSA) represents a risk for the spread of bacteria. This study characterized the S. aureus isolated from medical students, who were in their clinical rotation at a hospital in the city of Cali. Materials and Methods. 216 students participated in the study and 63 isolates of S. aureus were evaluated for susceptibility and PCR amplification of agr and mecA genes. The origin of MRSA isolates was established by analyzing agr polymorphisms. Results. A total of 29.2% of students were colonized by S. aureus and nasal carriage rate was 23.6% and 14.3% MRSA. Three agr groups (agr II, and agr III) were identified; the agr I group was the most common, with a 35% prevalence; this group is from community origin. Conclusion. The present study demonstrates that medical students carry S. aureus strains, with the threat of spreading them both to community and hospital environments.